2017
DOI: 10.3897/bdj.5.e13829
|View full text |Cite
|
Sign up to set email alerts
|

Hydro-edaphic conditions defining richness and species composition in savanna areas of the northern Brazilian Amazonia

Abstract: BackgroundStudies on plant communities in the Amazon have reported that different hydro-edaphic conditions can affect the richness and the species composition of different ecosystems. However, this aspect is poorly known in the different savanna habitats. Understanding how populations and plant communities are distributed in these open vegetation areas is important to improve the knowledge about which environmental variables influence the occurrence and diversity of plants in this type of regional ecosystem. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
4
0
3
Order By: Relevance
“…From an ecological standpoint, Coutinho (2016) considered that the ecology of the cerrado, with deep soils and water table, differs from that of the Amazonian savannas, where the soils are often waterlogged due to the presence of rocks lying at the surface or not far below it. Araújo et al (2017) found that the waterlogged savannas (also known as campinaranas) have considerable higher herbaceous plant diversity and abundance than the more drained sites. Similar sites in the Amazon were already described as swampy savannas (Pires-O'Brien, 1992).…”
Section: Affinities Of the Amazonian Savannasmentioning
confidence: 99%
“…From an ecological standpoint, Coutinho (2016) considered that the ecology of the cerrado, with deep soils and water table, differs from that of the Amazonian savannas, where the soils are often waterlogged due to the presence of rocks lying at the surface or not far below it. Araújo et al (2017) found that the waterlogged savannas (also known as campinaranas) have considerable higher herbaceous plant diversity and abundance than the more drained sites. Similar sites in the Amazon were already described as swampy savannas (Pires-O'Brien, 1992).…”
Section: Affinities Of the Amazonian Savannasmentioning
confidence: 99%
“…The savanna region of the state of Roraima is the largest savanna area of the Brazilian Amazon, occurring in the northern state of Roraima ( Barbosa et al 2007 ; Araújo et al 2017 ). The savanna area of Roraima is locally referred as lavrado , “ campos do rio Branco " or " campos de Roraima ", and covers an area of over 40,000 km 2 within the large Rio Branco-Rupununi landscape complex, which extends into the Republic of Guyana and Venezuela ( Barbosa and Fearnside 2005 , Barbosa and Campos 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…The current region is covered by savannas vegetation known locally as "lavrado" (Carneiro-Filho, 1992;Barbosa & Miranda, 2004;Barbosa et al, 2007;Nascimento & Lins, 2018), which consists of grasses and sedges, in open areas, and added with shrub and tree species in areas of more closed vegetation (Miranda & Absy, 2000;Barbosa & Miranda, 2004;Hollowell et al, 2007;Morais & Carvalho, 2015;Araújo et al, 2017). The "lavrado" is also formed by an undefined network of islands of forests dominated by Mauritia flexuosa L.f., being part of the drainage system sometimes associated with paleochannels, called "veredas" (Palm swamps) (Barbosa & Miranda, 2004;Morais & Carvalho, 2015).…”
Section: Vegetation Formationmentioning
confidence: 99%